The Construction and Reverse Construction of the Complete Arcs in the Projective 3-Space Over Galois Field GF(2) - Al-Mukhtar, A. SH. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The main purpose of this work is to find the complete arcs in the projective 3-space over Galois field GF(2), which is denoted by PG(3,2), by two methods and then we compare between the two methods